Design and Synthesis of 3,5-Disubstituted 1,2,4-Oxadiazole Containing Retinoids from a Retinoic Acid Receptor Agonist - Das, Bhaskar C. (2011)
We previously synthesized novel retinoid libraries, and after screening for bioactivity found one compound BT10 that functions as a specific agonist for retinoic acid receptors. This lead compound was further derivatized using SAR and LRD to obtain 3,5-disubstituted-1,2,4-oxadiazole-containing retinoids. The new oxadiazole (amide bioisosters)-containing retinoids (compounds 1, 2, 3, 4, 5, and 6) were synthesized in 42-65% yield by reacting with (E)-4-((3-ethyl,2-4,4,4-trimethylcyclohex-2-enylidene)methyl)benzoic acid and phenyl substituted amidoxime in DMF using CDI as the coupling reagent. The biological activities of the synthesized compounds are currently being evaluated.